Dalla complessità alla semplificazione: il contributo dell’Unità di Ricerca EPM ad un toolkit per la valutazione e gestione del rischio da sovraccarico meccanico e la prevenzione dei WMDSs / From complexity to simplification: contribution of the EPM Research Unit to producing a toolkit for risk assessment and management of biomechanical overload and WMSDs prevention - Occhipinti, E.; Colombini, D. (La Medicina del Lavoro, 2011)
«From complexity to simplification: contribution of the EPM Research Unit to producing a toolkit for risk assessment and management of biomechanical overload and WMSDs prevention». Background: When studying musculoskeletal disorders and their connection with working conditions (WMSDs), several factors of different nature (mechanical, organizational, psychophysical, individual) and their interrelationship have been considered important in general models for epidemiologic surveys and risk assessment and management. Hence the necessity of a “holistic” (that is to say complex, global, multifactorial and interdisciplinary) approach to MSD prevention, especially when establishing technical norms, guidelines and strategic plans of action at national or international level. On the other hand, considering the widespread presence of these factors and WMSDs in many working contexts, there is a great demand by OSH agencies and operators to develop “simple” tools for risk assessment and management, usable also by non-experts in both developed and developing countries. Objectives: Both these needs are perfectly justified but  are also to a certain extent in conflict. How can we address the problem, i.e., simplify complexity? Methods and criteria: The proposals are based on two essential criteria: 1) Act on a step-by-step approach using basic tools first and more complex tools only when necessary. 2) Take into account the complexity and the presence of multiple influencing factors at every step (even if with different degrees of in-depth analysis). The proposals are mainly developed within the framework of an IEA-WHO collaboration initiative for a “Toolkit for MSD prevention” but they are also derived from other converging issues (i.e. ISO application document of ISO series 11228 on manual handling). Results: The proposals consider: 1) A Basic Step devoted to preliminary occupational hazard identification and priority check by operative “key enter” questions (at this step all potential hazards - including those influencing WMSDs - should be considered). This step also can be carried out by non-experts with limited training. 2) First Step, focused on WMSDs risk factors, consisting of a “quick assessment” and mainly addressed to identifying 3 possible conditions: acceptable/no consequences; high risk present/redesign urgently needed; a more detailed analysis (via tools proposed in second step) is necessary. This step can also be carried out by non-experts with only limited training. 3) Second Step, where recognized tools (i.e. from international standards or guidelines) for risk (of WMSDs) estimation are used as a consequence of the first step outcome. Examples of such tools are “adaptations” of the Revised NIOSH Lifting Equation, Liberty Mutual Psychophysical Tables, OCRA Checklist, etc. These tools should be able to adequately take account of most of the influencing factors. For some particular working sectors (i.e. agriculture) these tools need to be specifically adapted. For particular working sectors a database could be envisaged where the most common tasks (with their “variants”) are “intrinsically” evaluated by experts and could provide non-experts with the relevant knowledge to be applied to the specific work context. This step can be carried out only by persons with some sort of specific training.